What is the Avatar? Fiction and Embodiment in Avatar-Based Singleplayer Computer Games. Revised and Commented Edition - Klevjer, Rune (Game Studies, 2022)
What are the characteristic features of avatar-based singleplayer videogames, from Super Mario Bros. to Grand Theft Auto? Rune Klevjer examines this question with a particular focus on issues of fictionality and realism, and their relation to cinema and Virtual Reality. Through close-up analysis and philosophical discussion, Klevjer argues that avatar-based gaming is a distinctive and dominant form of virtual self-embodiment in digital culture. This book is a revised edition of Rune Klevjer's pioneering work from 2007, featuring a new introduction by the author and afterword by Stephan Günzel, Jörg Sternagel, and Dieter Mersch.